Beliefs and Behaviours of Parents Regarding Antibiotic Use by Children - Sean M Bagshaw; James D Kellner (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine parents' beliefs and behaviours about antibiotic use by their children in the ambulatory setting.